A formação de docentes inclusivos: um desafio para a educação brasileira - Brandão, Carlos da Fonseca [UNESP]; Bezerra, Adriano Aparecido (My University, 2012)
Respect for differences is one of the most important subjects in debate in the Brazilian and World society today. It’s consensus that diversity education is very important to make humanity fairer and more equal. In this context, it’s necessary to separate real pedagogic actions from political demagogy. So, our objective in this paper is to enrich this discussion with the results of our project “Perspectives of teachers about the inclusion of special students in Programa UNESP de Educação de Jovens e Adultos”. These results will demonstrate a good example of inclusive education and will prove the inadequacy of training in special education offered to Brazilian university students. In our opinion, it’s impossible to believe in diversity education without appropriate training in inclusive education because this work requires accommodation of social, political, physical, religious, cognitive and cultural differences and this demands a skilled professional in all teaching methods.

O respeito às diferenças é um dos principais temas em debate na sociedade brasileira e mundial atualmentes, sendo a educação na (e para a) diversidade a coluna principal de uma humanidade mais justa e igualitária. Nesse contexto, é necessário que separemos ações concretas de demagogias polí- ticas e que valorizemos trabalhos que socializem sujeitos tradicionalmente excluídos do nosso sistema de ensino. Tendo isso em mente, nosso objetivo neste artigo é enriquecer essa discussão, apresentando alguns dos resultados obtidos no nosso projeto “Perspectivas dos professores sobre a inclusão de alunos especiais no Programa Unesp de Educação de Jovens e Adultos”. Esses resultados demonstrarão um bom exemplo de socialização educacional de indíviduos com deficiência e provarão a insuficiência da forma- ção em educação inclusiva oferecida aos graduandos brasileiros. Não acreditamos em educação na (e para a) diversidade sem a formação de docentes inclusivos, pois o trabalho nesse âmbito educativo exige um acolhimento sistemático das diferenças, sejam elas sociais, políticas, físicas, religiosas, culturais ou cognitivas, o que depende de profissionais capacitados nas diversas modalidades e formas de ensino.
Inclusive teachers formation: a challenge for brazilian education
Keywords: Special students; Diversity education; Inclusive education; Teacher formation; Respect for differences; Educação inclusiva; Formação de professores; Educação de jovens e adultos; Política educacional; Políticas públicas